ASSESSMENT OF NUTRITIONAL STATUS AND BEHAVIORAL CHARACTERISTICS OF ADHD CHILDREN (4-10 YEARS) IN SPECIAL SCHOOLS OF PUDUCHERRY - G. Haritha (Kongunadu Research Journal, 2025)
ADHD is one of the most common childhood brain disorders and can continue through adolescence and adulthood. The objective is to study the causes, nutritional status and behavioural characteristics of attention deficit hyperactivity disorder children aged 4-10 years in special need schools of Puducherry. The special need schools and the subjects was selected using purposive sampling technique to collect details on pre diagnosed attention deficit hyperactivity disorder children and other learning-disabled children, as the study was exclusive. The structured questionnaire was formulated to collect the details pertaining to the study. Further by using Statistical Package of Social Science, the mean results were calculated. The results of the study reveal that were majority of 63 percent of children with ADHD belong to first ordinal position, a higher value of 61.9 percent of male children were pre diagnosed with ADHD compare to female children of 58.3 percent. The major number of children was identified with combined type of ADHD. The maternal life style of ADHD children’s mother was found to be 70.4 percent were leading sedentary life style. The consanguineous marriage was highly prevalent in parents of ADHD children. The energy and calcium intake is found to be deficit and fat content was excess in all three-age group.  Eighty-three-point three percent of children’s dietary pattern was non vegetarian. The intake of fruits and vegetables was identified with less frequency of consumption which mainly contains all nutrients for brain development. The processed and miscellaneous food consumption frequency was found to be higher 79.6 and 59.3 percent respectively. The awareness of sugar free, casein free, Feingold diet and gluten free diet along with food exchange list were provided for parents through awareness program. Which indicates to avoid artificial or processed foods and additives and besides gluten free diet also plays major role of ADHD children behaviour. Thus, the change in diet pattern can help children with ADHD. Future research in supplementation of foods can majorly help the community to manage ADHD children.